Forces et paradoxes des dynamiques dites « inclusives » : Étude auprès d’enseignants en formation à l’École inclusive - Cendrine Mercier; Gaëlle Lefer-Sauvage (Éducation et Socialisation)
The inclusive school, which is a young paradigm still under construction, needs time to gradually take hold in the school environment and in teaching practices. Through the experiences of CAPPEI candidates, it is possible to understand the forces that facilitate the implementation of schooling for all, but also the paradoxes that prevent an inclusive dynamic in France. We cross the paradigmatic issues with biographical analysis, based on what the teacher has experienced in relation to his/her own professional and personal history. A qualitative analysis of 46 CAPPEI candidates highlighted the importance of professional (close to the medical field) and personal backgrounds in the understanding of the notion of need. We also note that previous non-conscious or implicit practices that are related to inclusion are the subject of the challenge of continuous training. Finally, representations that are obstacles to the inclusive dynamic through the notion of disability and normativity participate in slowing down this dynamic. Also, it appears that the personal and professional histories of teachers are involved in a parallel dynamic that is as complex as the political and cultural history of inclusion.